Eutectogels: The Multifaceted Soft Ionic Materials of Tomorrow - Mercadal, Pablo Agustin (2024)
Eutectogels, a rising category of soft materials, have recently garnered significant attention owing to their remarkable potential in various domains. This innovative class of materials consists of a eutectic solvent immobilized in a three-dimensional network structure. The use of eco-friendly and cost-effective eutectic solvents further emphasizes the appeal of these materials in multiple applications. Eutectogels exhibit key characteristics of most eutectic solvents, including environmental friendliness, facile preparation, low vapor pressure, and good ionic conductivity. Moreover, they can be tailored to display functionalities such as self-healing capability, adhesiveness, and antibacterial properties, which are facilitated by incorporating specific combinations of the eutectic mixture constituents. This perspective article delves into the current landscape and challenges associated with eutectogels, particularly focusing on their potential applications in CO2 separation, drug delivery systems, battery technologies, biocatalysis, and food packaging. By exploring these diverse realms, we aim to shed light on the transformative capabilities of eutectogels and the opportunities they present to address pressing industrial, academic, and environmental challenges.